ORGANIZATION OF DISTANCE EDUCATION ON THE EXAMPLE OF THE USE OF ELECTRONIC BOOKS - Okhunov, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The distance method of the educational process is one of the promising options for learning. This direction began to develop rapidly in connection with the improvement of digital technologies and the development of the Internet. Of course, the educational process based on a distance approach requires its own specific approaches, which are often not successful due to the transformation of traditional approaches into a distance one. In this article, based on many years of our own experience, we presented our visions of the mandatory requirements for conducting this type of educational process using e-textbooks as an example. The article will be useful not only for teachers of medical higher educational institutions, but also for other professional areas.